Daytime sleep disorders among patients with Parkinson’s disease in a tertiary medical centre in Kano, Northwestern Nigeria - Ahuoiza Hauwa Aliyu; Yahaya Mohammed; Jamila Bashir; Salihu Saleh Joji; Suleiman Baba Abdullahi; Nuhu Abubakar; Aliyu Ibrahim; Lukman Femi Owolabi (Pyramid Journal of Medicine, 2026)
Parkinson’s Disease (PD) is commonly associated with sleep disorders, which may manifest years before disease diagnosis. Excessive Daytime Sleepiness (EDS) is a common problem seen in People with PD (PwPD) which is found to worsen by the presence of concomitant insomnia (sleep fragmentation, shortened sleep duration, early awakening) and anti-Parkinson’s medications. Identifying its presence and provision of appropriate intervention could significantly improve their Quality of Life (QoL). Using a cross-sectional study design, 100 PwPD and 100 healthy controls were enrolled over a period of 10 months to assess the prevalence of EDS using the Scales for Outcome in Parkinson’s Disease-Sleep (SCOPA-S) diagnostic tool. The SCOPA-S index questionnaire identified EDS in 64% of PwPD who have significant daytime sleepiness, including falling asleep unexpectedly either during the day or in the evening (U=1722.5, p